Comparison of Inpatient Charges between Primary and Revision Total Hip Arthroplasties: A Study of Trends within the New York's Statewide Planning and Research Cooperative System - Passano, Brandon; Simcox, Trevor; Anil, Utkarsh; Lin, Charles; Barzideh, Omid; Schwarzkopf, Ran (The Journal of Hip Surgery, 2023)
The U.S. health care system continues to absorb greater costs for total hip arthroplasty (THA). The purpose of this study is to quantify inpatient charges for primary THA (pTHA) and revision THA (rTHA) and to review trends over the past decade. A New York statewide database was utilized to identify all inpatient elective pTHA and rTHA from 2010 to 2020. Nonelective indications were excluded. The primary outcome measure was total inpatient charges per encounter. Secondary outcomes included: accommodation charges, ancillary charges, and hospital THA volume. Subgroup analyses were performed based on rTHA indication and hospital volume. Total 256,879 pTHAs and 29,852 rTHAs were identified; 6,616 rTHAs were performed for instability, 5,976 for aseptic loosening, 5,155 for mechanical complications, 4,343 for infection, 3,014 for periprosthetic fracture, 1,427 for polyethylene wear, and 3,321 for other indications. Compared with pTHA, there were higher total, accommodation, and ancillary charges in the rTHA cohort (p < 0.001). High-volume centers achieved lower total charges for rTHA, lower accommodation charges for both cohorts, but higher ancillary charges for pTHA (p < 0.001). Between 2010 and 2020, total charges increased 46.6 and 76.2% for pTHA and rTHA, respectively. Inpatient costs of rTHA were significantly higher than that of pTHA. For rTHA, charges were highest for periprosthetic fracture and infection. Total inpatient charges of THA have greatly outpaced inflation over the past decade.
Keywords: arthroplasty; revision; charges; SPARCS; hip